A Retrospective Review Following the Addition of Clonidine to a Neonatal Abstinence Syndrome Treatment Algorithm - Bader, Mohammad Y.; Zaghloul, Nahla; Repholz, Ashley; Nagy, Nadia; Ahmed, Mohamed N.; Thompson, Leslie; Kylat, Ranjit I. (Frontiers in Pediatrics, 2021)
Objective: To investigate the outcomes associated with the implementation of a neonatal abstinence syndrome (NAS) treatment algorithm utilizing dual therapy with morphine sulfate and clonidine in a level four neonatal intensive care unit (NICU). Study Design: A cohort of neonates (greater than or equal to 35 weeks gestation) born at an academic tertiary medical center between January 1, 2015 and December 31, 2018 who were diagnosed with NAS were retrospectively evaluated following the implementation of a new NAS treatment algorithm. Neonates were categorized in two groups based on if they were treated pre- or post-implementation of the protocol. The primary efficacy outcome was length of hospital stay. Secondary outcomes included the incidence of adverse drug reactions, length of treatment for NAS, and maximum as well as total cumulative dose of each medication used to treat NAS. Results: The implementation of this NAS treatment algorithm significantly reduced the length of hospital stay (30 days vs 20 days, p=0.001). In addition, there was a significant decrease in duration of morphine sulfate exposure as well as cumulative dose of morphine required to successfully treat a neonate with NAS in the post-implementation group (26 days vs 15 days, p=0.002 and 6.9 mg/kg vs 3.4mg/kg, p=0.031). Conclusion: Addition of clonidine to morphine sulfate as initial therapy for NAS significantly reduced the cumulative exposure as well as duration of exposure to morphine sulfate compared to morphine monotherapy and decrease length of hospital stay.